An Evaluation of the Integral Housekeeping Supplies of One of the Resorts at San Bartolome, Novaliches Quezon City: Basis for Enhancing the Customer Level of Satisfaction: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The housekeeping department is the most important part of a resort because they areresponsible for the cleanliness, and they take satisfaction in keeping the resort comfortable, tobuild the ‘home away from home.’ Effective housekeeping can help to oversee and extinguishresort hazards. It is not just about cleanliness; it keeps work and guest areas organized and inorder. This study aims to identify what cleaning chemical supplies are needed in trainingactivities in a resort and what adjustments are made if the cleaning chemicals and suppliesare not available to enhance customer satisfaction.Customer satisfaction can be enhanced in terms of the employee’s performance, cleanliness,comfort, and guest satisfaction. However, there are problems encountered by the customers,such as customer complaints occurring because of some problem inside the guest room(malfunctioning air conditioning unit, clogged toilet, TV signal, etc...), but solutions have beenmade, including regular room check-ups and maintenance.To gain more knowledge and recognize what to do if there are not enough cleaning chemicalsand equipment in the resort, they have to maintain organized housekeeping supplies. Use thisstudy to gain a basic understanding of the importance of cleaning supplies that they could usein the future. Housekeepers will be able to get enough information to use for their work as theyimprove and know better about working hours. This study is to gather information abouthousekeeping cleaning supplies and what practices are needed to have successful duties.
Keywords: Business